Biomaterials for Helicobacter pylori therapy: therapeutic potential and future perspectives - Yongkang Lai; Wei Wei; Yiqi Du; Jie Gao; Zhaoshen Li (Gut Microbes)
Helicobacter pylori (H. pylori) is the main cause of gastric adenocarcinoma. However, the traditional antibiotic treatment of H. pylori is limited due to increased antibiotic resistance and low efficacy; low drug delivery efficiency and difficulties in eradicating H. pylori that is present intracellularly or in biofilms cause further setbacks. Biomaterials that can protect drugs against stomach acid, target lesions, control drug release, destroy biofilms, and exhibit unique antibacterial mechanisms and excellent biocompatibility have emerged as attractive tools for H. pylori eradication, particularly for drug-resistant strains. Herein, we review the virulence mechanisms, current drug treatments, and antibiotic resistance of H. pylori strains. Furthermore, recent advances in the development of biomaterials, including nanoparticles (such as lipid-based nanoparticles, polymeric nanoparticles, and inorganic nanoparticles), microspheres, and hydrogels, for effective and precise therapy of H. pylori and different types of therapeutic mechanisms, as well as future perspectives, have also been summarized.